REVIEW OF REVERSIONARY RIGHTS IN THE SOLD-FLAT AGREEMENT OF SONG CREATION ASSOCIATED WITH LAW NUMBER 28 OF 2014 ON COPYRIGHT - Utama, Atika Nur Rahmah; Ayu Palar, Miranda Risang; Muchtar, Helitha Novianty (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2024)
The copyright reversion provision or known as reversionary right contained in Article 18, 30, and 122 Law of the Republic Indonesia Number 28 of 2014 on Copyright is a legal substance that has been regulated by various countries in the world. This provision is intended to provide justice for creators whose rights are often violated in the implementation of copyright transfer agreements with a sold-flat mechanism. Indonesia Copyright Law is not specifically determined an implementing rules or guidelines to exercise this rights of reversions provisions. In its application, there have been rejections from record producer company such as in the case of Constitutional Court Decision Number 63/PUU-XIX/2021. This article is placed to review the implementation of reversionary rights provisions in Indonesia by analyzing national dan international provisions and court decisions with normative juridical methods and comparative law, as well as analytical and exploratory descriptive approaches. The implementation of reversionary rights provisions in Indonesia will raise challenges of weak legal understanding and disruption of rejection by record producers, which will weaken aspects of the implementation process. The provisions of the stages of the submission notifications process and documentation of reversionary rights in writing applied by the United States and the Netherlands can be something that Indonesia develops in strengthening the implementation process of reversionary rights provisions. To exercise and enforce their reversion rights, songwriters can renegotiate the agreement with the record producer, file for compensation with the commercial court, or also join the Collective Management Organization.